Acute Hospitalizations for Pneumonia in Adults in the United States in 2014. (4th October 2017) - Suaya, Jose; Harrison, Vannessa; McLaughlin, John; Chilson, Erica; Vietri, Jeffrey; Gessner, Bradford; Swerdlow, David; Isturiz, Raul
Abstract: Background: The burden of adult pneumonia is significant but not described uniformly. Most prior studies of pneumonia rates have used administrative claims data, with annual estimates of 1200−2000 hospitalizations per 100, 000 persons age ≥65. These studies typically include only pneumonias coded as a primary diagnosis (i.e., first diagnosis position of the claim). This approach may underestimate the true burden of pneumonia hospitalizations. We describe nationally-representative all-cause pneumonia hospitalization rates in US adults and compare incidence rates of pneumonia based on primary diagnosis only or any diagnosis (i.e., any claim position). Methods: We used the National Inpatient Sample of the Healthcare Cost and Utilization Project, which is a population-weighted, 20% sample of all US community hospitalizations. We included all adult (age ≥18) discharges for pneumonia in 2014 and calculated age-stratified annual incidence rates per 100, 000 population. Results: In 2014, there were >2.4 million hospitalizations with any pneumonia diagnosis in US adults, 33% had pneumonia as the primary diagnosis. Incidence of pneumonia as a primary diagnosis increased with age, ranging from 67 to 2493 hospitalizations per 100, 000 across age groups. Hospitalizations for pneumonia in any diagnosis position were 2–3 times higher and ranged from 202–6691 hospitalizations per 100, 000 (Table). Despite older adults having higher rates of pneumonia hospitalization, 38% of all pneumonia hospitalizations occurred in adults <65. Conclusion: Incidence rates of adult hospitalized pneumonia from administrative claims data depend largely on case definition. Rates based on a primary diagnosis of pneumonia only were considerably lower than rates where the case definition was expanded to any pneumonia diagnosis. Thus, the burden of pneumonia hospitalizations may be larger than previously estimated in claims database studies limited only to pneumonia as a primary diagnosis. Additionally, despite the lower incidence in adults <65 vs ≥65, 18–64 year-olds accounted for 38% of all pneumonia hospitalizations. Future work should attempt to define the full burden of pneumonia in younger adults, especially among those at increased risk. Disclosures: J. Suaya, Pfizer Inc: Employee and Shareholder, Salary; V. Harrison, Pfizer Inc: Research Contractor, Salary; J. McLaughlin, Pfizer Inc: Employee and Shareholder, Salary; E. Chilson, Pfizer Inc: Employee and Shareholder, Salary; J. Vietri, Pfizer Inc: Employee and Shareholder, Salary; B. Gessner, Pfizer Inc: Employee and Shareholder, Salary; D. Swerdlow, Pfizer Inc: Employee and Shareholder, Salary; R. Isturiz, Pfizer Inc: Employee and Shareholder, Salary